TruePrime is a novel method for whole-genome amplification from single cells based on TthPrimPol - Ángel J. Picher (Nature Portfolio, 2016)
Single cell genomic analysis needs DNA amplification with high fidelity and accuracy. Here, the authors devise a novel multiple displacement amplification method called TruePrime that is based in Thermus thermophilusPrimPol and Phi29 DNA polymerase, and demonstrate its utility and accuracy.